2009
DOI: 10.5194/angeo-27-623-2009
|View full text |Cite
|
Sign up to set email alerts
|

Fine structures and dynamics in auroral initial brightening at substorm onsets

Abstract: Abstract. We show four auroral initial brightening events at substorm onsets focusing on fine structures and their longitudinal dynamics, which were observed by all-sky TV cameras (30-Hz sampling) on January 2008, in Canada. For two initial brightenings started in the field of views of the cameras, we found that they started at longitudinal segments with a size of less than ∼30-60 km. One brightening expanded with wavy structures and the other expanded as a straight arc. Although the two events had different s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
63
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 19 publications
(16 reference statements)
11
63
1
Order By: Relevance
“…In particular, the slowly moving beads in the first stage have never been reported in previous studies [Donovan et al, 2006;Sakaguchi et al, 2009]. Very recently, Kataoka et al [2011], using an electron multiplier charge-coupled device (EMCCD) camera with a narrow FOV, demonstrated that smaller-scale auroral forms (on a scale of a few/several km) appear in a breakup arc in a few minutes before onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the slowly moving beads in the first stage have never been reported in previous studies [Donovan et al, 2006;Sakaguchi et al, 2009]. Very recently, Kataoka et al [2011], using an electron multiplier charge-coupled device (EMCCD) camera with a narrow FOV, demonstrated that smaller-scale auroral forms (on a scale of a few/several km) appear in a breakup arc in a few minutes before onset.…”
Section: Discussionmentioning
confidence: 99%
“…The scale of the beads and their separation are typically on the order of the gyroradius of 1-10 keV protons in the source magnetosphere. Thus, as suggested by Liang et al [2008] and Sakaguchi et al [2009], the plasma instability creating the beads in the primary stage of their development would not be a pure MHD scale process but include kinetic effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This filter passes 844.6 nm prompt emission from Oxygen molecule, as a result of both direct excitation and dissociative excitation. Breakup aurora is known as "ray" aurora [Sakaguchi et al, 2009a[Sakaguchi et al, , 2009b which has electron precipitation with the broadband energy range [Mende et al, 2003]. The 844.6 nm is a prompt emission, capable of capturing the rapid variation of both hard and soft electrons associated with the auroral breakup.…”
Section: Instrumentationmentioning
confidence: 99%
“…In recent years there have been many studies of auroral beads from data acquired by high resolution (temporal and spatial) ground-based all-sky imagers (ASIs) [e.g., Friedrich et al, 2001;Kepko et al, 2009;Sakaguchi et al, 2009;Rae et al, 2009Rae et al, , 2010Motoba et al, 2012;Murphy et al, 2014;Kalmoni et al, 2015] in which beads are reported to have spatial scales, or wavelengths, in the range 30-150 km in the ionosphere. Sakaguchi et al [2009] reported two case studies of substorm onset arcs which exhibited beading with spatial scales of 30-60 km in the ionosphere. This scale closely corresponds to the ion gyro radius of 1-10 keV protons in the plasma sheet at 10 R E , where the magnetic field strength is~12 nT.…”
Section: Introductionmentioning
confidence: 99%